Vertical transmission of St. Louis encephalitis virus in Culex quinquefasciatus (Diptera: Culicidae) in Córdoba, Argentina - Flores, Fernando Sebastián (2010)
Arbovirus vector transmission is interrupted when vector abundance decreases or disappears in temperate regions during the winter season. Although the primary overwintering mechanism for many arboviruses in nature remains unknown, vertical transmission is one potential mechanism. Vertical transmission functions as an overwintering mechanism for St. Louis encephalitis virus (SLEV) in temperate areas of Argentina, where SLEV is endemic. The aim of this project was to detect vertical transmission of SLEV in Culex quinquefasciatus mosquitoes. Under laboratory conditions, SLEV vertical transmission (3.4 minimum infection rates) was detected in larvae (1:256) and adults F1 (1:406). There were no positive larvae for SLEV among over 2011 analyzed individuals collected in nature. This is the first study to confirm experimental vertical transmission of SLEV in Cx. quinquefasciatus populations from Argentina, though additional overwintering mechanisms (e.g., nontraditional vectors such as ticks and nondiapausing female mosquitoes) should be considered.